2017
DOI: 10.1139/cjps-2016-0363
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Aconitate hydratase 4 (Aco4) from soybean

Abstract: Aconitase catalyzes the reversible isomerization of two tricarboxylic acids, citrate and isocitrate, during the Krebs cycle. Five aconitase genes, namely, Aco1, Aco2, Aco3, Aco4, and Aco5, have been identified in soybean. Previously, Aco4 was mapped on chromosome 11. The purpose of this investigation was to isolate and sequence the candidate gene for Aco4. We mapped the Aco4 gene to a 148 kb region on chromosome 11 that contained 19 predicted genes. One of these, Glyma.11G080600, codes for aconitate hydratase.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Collectively, the above results suggest that the OAA pathway is the main pathway for oxalate and acetate biosynthesis under alkali stress. However, notably, the glycolate/glyoxylate pathway might also be modified in grapevine roots under alkali stress, as indicated by the significant increase in the phosphorylation level of aconitate hydratase (aconitase), a key protein in the glycolate/glyoxylate pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the above results suggest that the OAA pathway is the main pathway for oxalate and acetate biosynthesis under alkali stress. However, notably, the glycolate/glyoxylate pathway might also be modified in grapevine roots under alkali stress, as indicated by the significant increase in the phosphorylation level of aconitate hydratase (aconitase), a key protein in the glycolate/glyoxylate pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…1). Coleman et al (2016) also found that SNP substitutions in the exon of the Aco4 gene in two soybean cultivars resulted in amino acid changes and different protein sequences. The authors hypothesized that these differences could produce different protein structures and aconitase isozyme patterns.…”
Section: Discussionmentioning
confidence: 89%
“…Recent soybean studies identified aconitase isozymes allelic variation in homozygous cultivars exposed to environmental stimuli (Espinosa et al, 2015;Coleman et al, 2016 (Rouault and Klausner 1996;Sadka et al, 2000;Shlizerman et al, 2007).The Krebs cycle generates energy for organism's metabolic processes (Schnarrenberger and Martin, 2002). Aconitase is comprised of iron-sulfur cluster (3Fe-4S) in its inactive form and is activated through the binding of a fourth free iron to form 4Fe-4S cluster (Zhou and Ragan 1995;Gardner 1997;Shlizerman et al, 2007).…”
Section: Epigenetic Genetic and Morphological Responses To Environmmentioning
confidence: 99%
See 2 more Smart Citations